Pengaruh Motivasi dan Komitmen Organisasi terhadap Prestasi Kerja Karyawan Emela Garment Kota Bogor - Wahyu Aji Wibowo; Sri Harini; Diah Pranitasari; Meldasari Said; Acai Sudirman (Jurnal Manajemen, 2022)
This study aimed to determine the effect of motivation and organizational commitment on the work performance of Emela Garment employees in Bogor City. The population and sample are 55 daily employees using a sampling technique, namely the saturated sample technique. The results of the data instrument test use validity and reliability, and statement items are valid and reliable. Analysis of research data includes multiple regression analysis, correlation, determination, and significance test simultaneously (F test) and partial (t-test). The results of the study through multiple regression analysis of motivation and organizational commitment variables have a positive and significant effect on employee work performance a. The results of the F test state that motivation and organizational commitment simultaneously ve a positive and significant effect on work performance. While the results of the t-test state that partially the motivational variable has a positive and significant effect on work performance, and organizational commitment has a positive and significant effect on the work performance of Emela Garment employees in Bogor City. Suggestions for companies should manage employee cohesiveness to be able to work as a team, maintain and maintain relationships with employees, and reward employees who take the initiative.